Entrepreneurial Intention Among MBA Graduates in UTHM - Mohammad Haidzir, Humaira; Rashid, Umi Kartini (Research in Management of Technology and Business, 2023)
Throughout the year, despite the fact that entrepreneurial intention had been widely studied and discussed by researchers around the world, numerous categories of studies, such as entrepreneurial intention among women, the youth generation, the educated individual, and others, had been conducted, the question of their applicability in the local context had remained. There had been a lack of study in this area done especially for the cohort of MBA graduates. Therefore, this study focused on the MBA graduates in UTHM. Although MBA graduates were generally thought to be well-educated, the debate remains as to what variables influence their desire to pursue entrepreneurship. Therefore, the purpose of this study was to identify entrepreneurial intention among MBA graduates in UTHM by expanding Ajzen’s (1991) Theory of Planned Behaviour (TPB). Entrepreneurial intention was the dependent variable in this study. Attitude, subjective norm (SN), perceived behavioural control (PBC) and entrepreneurial knowledge (EK), on the other hand, serve as independent variables. 44 respondents had involved in this study and the Statistical Packages for Social Science (SPSS) software was used to analyse data. The analysis consisted of descriptive analysis and correlational analysis. The result demonstrated that attitude and perceived behaviour control were the major factors affecting entrepreneurial intention among MBA graduates in UTHM. However, subjective norm, and entrepreneurial knowledge had no significant relationship with entrepreneurial intention among MBA graduates in UTHM. Finally, future research needs to concentrate on a broader scope of research from area coverage that encompasses all MBA graduates in Johor in order to investigate a more comprehensive Johor context. Allowing for a longer duration, not only to reach more respondents but also to provide ample time for participants to react rightly without feeling rushed and ultimately provide more meaningful findings, is the second most important thing that needs to be considered.